Representasi Bentuk Pertunjukan Tari Rondhek di Desa Banyumanis Kabupaten Jepara - Kartika Anggraini, Chintya; Putri, Rimasari Pramesti; Kusumastuti, Eny (Dinasti Research, 2025)
Folk art, particularly traditional dance, serves as a powerful reflection of local culture and plays a crucial role in preserving community values. The Rondhek Dance in Banyumanis Village, Jepara, is a testament to this, representing a vibrant folk art that remains well-preserved and carries profound historical, social, and aesthetic significance. This dance seamlessly blends movement elements from the Reog and Ledhek traditions, creating a dynamic choreography imbued with symbols of togetherness and mutual cooperation. This research aims to meticulously analyze the performance form of the Rondhek Dance. Employing a qualitative methodology with a choreological approach , data was gathered through observation, interviews with Mr. Kaolan (the dance creator and head of the studio) as well as the dancers, and documentation. The findings indicate that the Rondhek Dance features distinct performance characteristics. These include beautiful stage makeup that highlights the brave yet gentle female warrior character , red and yellow costumes symbolizing courage and cheerfulness , a musical accompaniment combining Javanese gamelan and drums with gending lancaran and meaningful lyrics , and simple floor patterns like circles and straight lines signifying unity. Ultimately, the Rondhek Dance functions not merely as entertainment, but also as a vital means of preserving tradition, the spirit of mutual cooperation, and the cultural identity of the Banyumanis community.